A NEW MODEL FOR A MAGNETORECEPTOR IN HOMING PIGEONS BASED ON INTERACTING CLUSTERS OF SUPERPARAMAGNETIC MAGNETITE - Davila A.F.; Petersen N.; Fleissner G.; Winklhofer M. (My University, 2003)
We present a new model of a magnetoreceptor based on the mutual interactions of adjacent clusters of superparamagnetic (SP) particles. The model takes into account previous microscopic results on tissue samples of homing pigeons: In the putative magnetoreceptor tissue, clusters of SP magnetite are found in close neighbourhood to each other, often even in alignment, like a string of perls. Depending on the direction of the magnetic field, the clusters attract or repel each other, which results in mechanical strain in the tissue associated with the clusters. It will be shown that the magnetic- field dependent strain is sufficiently large to be detected by cellular strain receptors. Our new theory is supported by model experiments on ferrofluid droplets to simulate the behaviour of the clusters in a variable magnetic fields.